Improving the manufacturing technology of sensing gas sensors based on zinc oxide by using the method of magnetron sputtering on direct current - Miasoiedova, Alona; Minska, Natalia; Shevchenko, Roman; Azarenkо Olena; Lukashenko, Viktoriia; Kyrychenko, Oksana; Zemlianskyi, Oleh; Trefilova, Larisa; Kamyshentsev, Gennady; Melezhyk, Roman (Eastern-European Journal of Enterprise Technologies, 2023)
A gas sensor based on zinc oxide obtained by magnetron spraying at direct current was investigated. There are methods of deposition of zinc oxide nanostructures such as thermal evaporation, chemical vapor deposition, organometallic chemical vapor deposition, magnetron sputtering, pulsed laser deposition, and hydrothermal process. The least investigated is magnetron sputtering. To obtain films, a vacuum unit VUP-5M with an original material-saving magnetron was used. Studies into the sensitivity and speed of the gas sensor based on ZnO with respect to the target gas – ethanol of different concentrations – were carried out. The resulting experimental dependences of the sensitivity of the gas sensor on the concentration of the target gas demonstrate that with increasing concentration of the target gas, the resistance decreased while the sensitivity of the sample increased. It was established that the change in the resistance of the test sample is proportional to the change in the concentration of the target gas. After the sensor surface becomes saturated with adsorbed molecules, the resistance no longer decreases, even if the gas concentration continues to increase. The reaction of the gas sensor to the target gas – ethanol – at concentrations above 150 ppm was almost absent. The time required to achieve the maximum response value should be lower at higher target gas concentrations. Sensitivity reaction repeatability studies were conducted to measure the resistance of a gas sensor based on ZnO in a target gas atmosphere with a concentration of 150 ppm. It was found that the gas sensor demonstrates excellent stability and consistent sensitivity reaction when re-exposed to the target gas – ethanol. It was established that the reaction time of a gas sensor based on ZnO to the target gas at each repeated exposure does not exceed 10 s. This repeatability index allows us to assert the stability of the ZnO-based gas sensor in an ethanol atmosphere under standard conditions